An Analytical Study Of Effective Time As A Physical Indicator In 1st Proffessional League Of Football. - Houcine, Djaballah; Benabderrahmane , Sid Ali (Journal of Sport Science Technology and Physical Activities, 2021)
The Object of the study aims to evaluate the effective time as a physical indicator in 1st Professional League of Football of Algeria, for this purpose, we used the analytical descriptive method using the note method by recording on a sample composed of 20 matches chosen at random, and for data collection, we used spss23. After collecting the results and having treated them statistically, we found that the level of actual play as one of the indicators of physical performance is relatively weak, as it reached the limits of 49.08 d, noting that this indicator in high-level matches ranges between 55'- 60' d and more. In addition to the decline in physical fitness during the second half, the analysis also showed that the total playing sequences are limited on a sequence 1" – 20". Also, playing in the entirety of the game is classified as a non-influential player who prevails.